Genome‐wide association mapping for field and seedling resistance to the emerging Puccinia graminis f. sp. tritici race TTRTF in wheat. Issue 4 (20th October 2022) - Negash, Tamrat; Edae, Erena Aka; Tilahun, Lidiya; Anderson, James A.; Rouse, Matthew N.; Bajgain, Prabin
Abstract: Stem rust of wheat ( Triticum spp.), caused by Puccinia graminis f. sp. tritici ( Pgt ), is one of the most impactful wheat diseases because of its threat to global wheat production. While disease mitigation has primarily been achieved through the deployment of resistant wheat varieties, emerging new virulent races continue to pose risks to the crop. For example, races such as Ug99 (TTKSK), TKTTF, and TTRTF have caused epidemics in different wheat growing regions of the world in recent years. A continual search for new and effective sources of resistance is therefore necessary to safeguard wheat production. This study assessed a breeding panel from the Ethiopian Institute of Agricultural Research (EIAR) wheat breeding program for seedling and field plant resistance to TTRTF and reports genomic regions conferring resistance to TTRTF. Trait correlations ( r ) were medium to strong (range = .38–.71) and heritabilities were moderate (.32–.56). Association analysis for resistance to TTRTF resulted in detection of 20 markers in 11 chromosomes; the marker S1B_175439851 was associated with resistance at both seedling and adult plant stages. Models with two to four QTL combinations reduced seedling and field disease severity by 12–48 and 9–17%, respectively. Genomic prediction for TTRTF resistance resulted in low to moderately‐high predictions (mean correlations of .25–.47). Identification of resistant lines and QTL in the EIAR population is expected to assist in selection toward improved resistance to TTRTF. Specifically, the application of genomic selection (GS) in identifying resistant lines in future related breeding populations will further assist breeding efforts against this new stem rust pathogen race. Core Ideas: Stem rust threatens wheat production in all wheat growing regions of the world. Continual search for resistance genes is needed to safeguard wheat from new races such as TTRTF. QTL associated with TTRTF resistance can reduce stem rust severity by up to 48% when deployed in combinations. By predicting resistance in future populations, GS could aid in selection of resistant lines.